Acute Pseudogout Flare After Intra-Articular Platelet-Rich Plasma Injection: A Case Report - Emily Andrews; Christopher Mulholland (Clinical Journal of Sport Medicine, 2026)
Abstract: Platelet-rich plasma (PRP) is increasingly used for the treatment of knee osteoarthritis (OA), especially in younger patients. Adverse effects are rare but can include synovitis and effusions. In this case, we present a 43-year-old woman with no history of calcium pyrophosphate deposition disease (CPPD) developed acute swelling and stiffness of the knee within 1 h after a leukocyte-poor PRP injection. Synovial fluid analysis revealed positively birefringent rhomboid-shaped crystals, confirming pseudogout. She was treated conservatively with NSAIDs and physical therapy, with complete symptom resolution in 2 weeks. This case highlights a rare complication of PRP injection, underscoring the importance of considering subclinical CPPD in patients with early onset OA. Pseudogout should be discussed as a potential, though uncommon, risk when counseling patients about PRP therapy.